Spawning periodicity of Mystus bleekeri (Day) from the river Padma of Bangladesh - Musa, A S M; Bhuiyan, Abdus Salam (Indian Journal of Fisheries, 2016)
Studies were conducted on the spawning periodicity of Mystus bleekeri (Day) from the river Padma of Bangladesh. A total of550 specimens (240 males and 309 females) of M. bleekeri (Day) were collected from different fish landing centres ofRajshahi during the period from April, 2004 to March, 2005. Five maturity stages of ovary viz., immature, maturing, mature,ripe and spent were observed. The high values of GSI during June, July and August indicated that these months were themain spawning period of the species and the fish breeds only once a year.